Strategy to Enhance Hotel Customer Satisfaction by Optimizing Service Quality, Emotions, and Trust at Shofa Marwah Hotel Palembang - Lestari, Widi Dwi; Artina, Nyimas (Jurnal Multidisiplin Sahombu, 2025)
This study analyzes strategies for increasing customer satisfaction through service quality, trust, and emotional factors at Shofa Marwah Hotel Palembang. In the competitive hospitality industry, customer satisfaction is crucial for loyalty and competitiveness. The research employs a quantitative approach using multiple linear regression analysis, based on data collected from questionnaires distributed to 100 customers over the past six months. The results indicate that service quality, trust, and emotional factors significantly influence customer satisfaction (significance value <0.05). Simultaneously, these three variables show a significant effect, with an F-calculated value higher than the F-table and a significance of 0.000. The coefficient of determination (Adjusted R Square) of 0.641 suggests that 64.1% of customer satisfaction variation is explained by these three variables. These findings highlight the importance of optimization strategies in enhancing customer satisfaction at the hotel.